COVERS Neonatal Pain Scale: Development and Validation - Ivan L. Hand; Lawrence Noble; Donna Geiss; Laura Wozniak; Charles Hall (International Journal of Pediatrics)
Newborns and infants are often exposed to painful procedures during hospitalization. Several different scales have been validated to assess pain in specific populations of pediatric patients, but no single scale can easily and accurately assess pain in all newborns and infants regardless of gestational age and disease state. A new pain scale was developed, the COVERS scale, which incorporates 6 physiological and behavioral measures for scoring. Newborns admitted to the Neonatal Intensive Care Unit or Well Baby Nursery were evaluated for pain/discomfort during two procedures, a heel prick and a diaper change. Pain was assessed using indicators from three previously established scales (CRIES, the Premature Infant Pain Profile, and the Neonatal Infant Pain Scale), as well as the COVERS Scale, depending upon gestational age. Premature infant testing resulted in similar pain assessments using the COVERS and PIPP scales with an r=0.84. For the full-term infants, the COVERS scale and NIPS scale resulted in similar pain assessments with an r=0.95. The COVERS scale is a valid pain scale that can be used in the clinical setting to assess pain in newborns and infants and is universally applicable to all neonates, regardless of their age or physiological state.